The Didactic of Sustainable Development Terms in Science Education - Seker, Fatih; Aydinli, Bahattin (European Journal of Social Science Education and Research, 2016)
Nowadays, sustainable development is frequently recited in science education also. There are various definitions which are distilled and extracted from educational research. However, the definitions are ambiguous and somehow contrary to each other. Generally, sustainable development was settled on the triangle of ecology, economy and society. Additionally, it has participation with biodiversity, energy resources, recycling and clean environment. Beside these, socioeconomic issues are one of the functional part of it. Here, it is handled with didactic perspective for incorporation to educational program. And it is concluded that sustainable development has participatory democratic structure. And it opens a new road in decision making.